1988
DOI: 10.1111/j.1540-6261.1988.tb03950.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradaily Price‐Volume Adjustments of NYSE Stocks to Unexpected Earnings

Abstract: The speed and path of adjustment in stocks to the degree of earnings surprise in their quarterly announcements are studied using price‐volume transactions data. A differential price‐adjustmentp rocess was observed,w ith stocks having large,p ositive earnings surprises experiencing a faster adjustment compared with those stocks with negative earnings surprises. Volume, transaction frequency, and size were found to be directly related to the absolute degree of surprise,b ut very favorablee arnings‐surprises tock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 31 publications
1
24
1
2
Order By: Relevance
“…We also find that, at 90 minutes, the process lasts 30 minutes longer for the non-members of an index, since we find no significant abnormal price reaction for the time interval (+61;+90) for the 58 ad hoc disclosures of the index members. Compared with the results of previous intra-day event studies, our price adjustment processes are slower than the process for earnings and dividend announcements found by Patell and Wolfson (1984), for unexpected earnings releases found by Woodruff and Senchak (1988), and for the announcement of new equity issues found by Barclay and Litzenberger (1988). However, the price adjustment processes of our study are still much faster than the eight hours for earnings announcements found by Jennings and Starks (1985), the five hours following announcements of takeovers found by Smith et al (1997), and the four hours following trading halts found by Lee at al.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…We also find that, at 90 minutes, the process lasts 30 minutes longer for the non-members of an index, since we find no significant abnormal price reaction for the time interval (+61;+90) for the 58 ad hoc disclosures of the index members. Compared with the results of previous intra-day event studies, our price adjustment processes are slower than the process for earnings and dividend announcements found by Patell and Wolfson (1984), for unexpected earnings releases found by Woodruff and Senchak (1988), and for the announcement of new equity issues found by Barclay and Litzenberger (1988). However, the price adjustment processes of our study are still much faster than the eight hours for earnings announcements found by Jennings and Starks (1985), the five hours following announcements of takeovers found by Smith et al (1997), and the four hours following trading halts found by Lee at al.…”
Section: Discussioncontrasting
confidence: 39%
“…Besides, they observe moderately abnormal price reactions in the minus 90 to minus 30 minutes interval before the announcements. Woodruff and Senchak (1988) analyze intraday price reactions caused by unexpected earnings results. They find price reactions occurring up to one hour after the announcements.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Dravid (1987Dravid ( ), 1962Dravid ( -1981 dö-nemi için hisse bölünmesi haberlerinin hisse oynaklığını arttırdığını belirlemiştir. Woodruff ve Senchack (1988), 1980'de Amerikan piyasalarında şirketlerin kendileri hakkında açıklamış oldukları olumlu haberlerin hisse fiyatlarını hızlı bir şekilde arttırdığı sonucuna ulaşmışlardır. Woolridge ve Snow (1990), yeni ürün tanıtımlarının ilgili hisse senedi yatırımcılarına pozitif aşırı getiriler sağladığını belirlemişlerdir.…”
Section: Literatür çAlışmasıunclassified
“…Austin (1993), 1991 yılında alınan patent ödülü duyurularının pozitif aşırı getiriler elde edilmesini sağladığını belirlemiştir. Yoon ve Starks (1995), 1969-1988 yılları arasında temettü haberlerinin genellikle pozitif getiriler elde edilmesini sağladığı belirlemiştir. Bajaj ve Vijh (1995);1962-1987 arasın-da kar ve temettü duyurularının hisse senetlerinin işlem hacmi miktarını arttırdığını belirlemişlerdir.…”
Section: Literatür çAlışmasıunclassified
“…[25] identified a different stock price adjustment process for unrealized information set forth in analysts' revisions of earnings estimates. [26] observed the largest adjustment of stock prices to the most favorable earnings news along with higher trading volume upon announcement of unexpected earnings for a sample of NYSE stocks.…”
Section: Analysts' Coverage Influences Earnings Surprisesmentioning
confidence: 99%